2020
DOI: 10.31871/wjir.8.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Heritability and Cluster Analysis in Some Accessions of Pepper (Capsicum Spp)

Abstract: Morphological and cytological evaluation of pepper accessions is important for breeding and improvement programme on the crop. The lack of understanding on the genetic variation of pepper accessions has led to little progress in breeding and improvement of the crop. Therefore, the objectives of this study were to characterize some available pepper accessions based on morphological, agronomic and cytological characters and their suitability for subsequent use in breeding programme. The field experiment was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Therefore, correlation and path analyses can benefit trait selection. Estimating the genetic variability and determining the nature of the relationship among the variables is a significant step toward genotype selection and improvement programs (Ishaya et al, 2020). The correlation analysis revealed that choosing almost all traits for use as selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, correlation and path analyses can benefit trait selection. Estimating the genetic variability and determining the nature of the relationship among the variables is a significant step toward genotype selection and improvement programs (Ishaya et al, 2020). The correlation analysis revealed that choosing almost all traits for use as selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Rani (2020) also had similar study that reported highest GCV and PCV for chlorophyll b among the other studied traits. High values of GCV and PCV were an indication of high genetic variability among the developed BC 2 F 1 populations thus there is scope for improvement of these characters through simple selection (Ishaya et al 2020). However, in backcross populations the lowest GCV values were depicted by plant spread, number of primary branches and fruit length.…”
Section: Genotypic and Phenotypic Coe Cient Of Variancesmentioning
confidence: 99%